2004
DOI: 10.1172/jci21309
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting organ innervation

Abstract: Neurotrophic growth factors, including nerve growth factor (NGF) and glialderived neurotrophic factor (GDNF), have well-established roles in promoting the innervation of target tissues, yet little is known about how the temporal and organ-specific expression of these factors is regulated. A new study (see the related article beginning on page 876) reveals that NGF is a direct target of the well-characterized peptide factor endothelin-1 (ET-1), and that ET-1-induced NGF expression is required for sympathetic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…However, this study raised the interesting possibility that Sprouty regulates GPCRligand mediated biological processes. It is notable that enteric nerve development is regulated by GDNF and endothelin-3 (Angrist et al, 1996;Hempstead, 2004). Therefore, the enteric nerve dysplasia phenotype of Sprouty2 KO mice may be partly explained by hypersignaling of ET-3 (Taketomi et al, 2005).…”
Section: Sprouty4 Inhibits Pip 2 Hydrolysis T Ayada Et Almentioning
confidence: 99%
“…However, this study raised the interesting possibility that Sprouty regulates GPCRligand mediated biological processes. It is notable that enteric nerve development is regulated by GDNF and endothelin-3 (Angrist et al, 1996;Hempstead, 2004). Therefore, the enteric nerve dysplasia phenotype of Sprouty2 KO mice may be partly explained by hypersignaling of ET-3 (Taketomi et al, 2005).…”
Section: Sprouty4 Inhibits Pip 2 Hydrolysis T Ayada Et Almentioning
confidence: 99%
“…More recently, BDNF has been shown to act as a neuromodulator of the central rhythmogenic respiratory circuits (68,69).…”
Section: Expression Of Polycomb Group Genes In the Emc-eshoxa1-15mentioning
confidence: 99%
“…Although it has been reported that the physiological origin of this defect is the presence of an ectopic neuronal circuit affecting the respiration-controlling region in the brain of the mutant embryos (114), little is known about the molecular causes that lead to the alteration of normal neurogenesis in this region. The identification by microarray analyses of the putative Hoxa1 target gene, BDNF, whose gene product acts as a neuromodulator of the central rhythmogenic respiratory circuits (69), may provide an additional clue about the molecular events involved in the perinatal lethality of the Hoxa1 homozygous mice. Analysis of the expression of the additional brain-related Hoxa1 putative targets in this region of the brain in mutant embryos may help to elucidate the cascade of genetic events that induces the formation of novel neuronal circuits.…”
Section: Hoxa1 ϫ/ϫ Es Cells Express Lower Levels Of Genes Involved Inmentioning
confidence: 99%
“…In the central nervous system (CNS), EDNs are expressed by endothelial cells (Yoshimoto et al 1990), neurones (Lee et al 1990), astrocytes (MacCumber et al 1990) and microglial cells (Wu et al 2006). EDNs regulate neuronal activity (Inoue et al 1989;Hempstead 2004), development (Yanagisawa et al 1998) and injury (Hama et al 1997;Siren et al 2000).…”
mentioning
confidence: 99%